I Must Obey The Father's Law: The Imaginary and The Symbolic Order in the Legend of Teluk Awur - Khurosan, Herpin Nopiandi; Faalih, Muhammad (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
The aim of the article is to address how the narrative structure of The Legend of Teluk Awur was constructed by primordial-individual self-structures. This article study focuses on how the narrative construction of The Legend of Teluk Awur is constructed, and how the self-construction in the form of the imaginary and the symbolic order of the legend is manifested. The data collection uses interviews with prominent residents of Teluk Awur Village about the narrative structure of the legend. The finding indicates that the narrative structure of The Legend of Teluk Awur represents an axis of desires of its character. That can be evident that the narrative structure of The Legend of Teluk Awur was constructed by the primordial-individual self-structure in the form of the imaginary and the symbolic order.